Analysis Of Secondary School Students’ Critical Thinking Skill In Learning Energy In Living System - Turino Adi Irawan; Sentot Budi Rahardjo; Sarwanto Sarwanto (Pancaran Pendidikan, 2017)
This study tried to describe the energy in daily life learning to train students' critical thinking skills. Improving critical thinking through learning in school is an effort in enlightening the quality of national education and Indonesian students' readiness to face the globalisation era which is full of challenge and sense of climate’ life that are very competitive. It was important to investigate the learning of energy in living systems in order to train the critical thinking skills because nowadays energy becomes a global issue which relates to the future life. This study utilised a qualitative method. The data were collected by the teacher’s documentation and depth interview. The data were then analysed, described, and interpreted comprehensively. Data analysis result gotten the teacher did not instruct and concentrate yet to the critical thinking. The root problem was the teacher did not show that learning guideline and comprehension that can lead to student critical thinking.